MEMBANGUN SISTEM INFORMASI MANAJEMEN PENDIDIKAN PADA TK XAVERIUS KOTABUMI LAMPUNG UTARA - Bangsawan, Laksamana (Jurnal Informatika, 2015)
Xaverius kindergarten of Kotabumi is a school for early childhood in it is the data collection process is still using a hand writing by the teacher and then typed using microsoft word 2007 and made brochure until needs long time and uneffective in delivery of information. This system to design an education management information system application using the web at Xaverius kinder garten of kotabumi. The system software developed with using PHP, MySQL, and the browser Internet Explorer or Mozilla Firefox also and some helper software such as Macromedia Dreamweaver. This information system is working to be able to present and process information such as profiles Xavier kindergarten school, teacher the data and student the data. The purpose of this information system is to present and disseminate information to good users and can update the contents of the information contained on the web with ease at the desired time.Â Keywords : Information Systems TK Xaverius Kotabumi, Web